Effect of Aging on the Adsorption of Tetracycline by Humic Acid: Insight into the Morphology and Chemical Composition - Chunli Zheng; Fei He; Zhiwu Cao; Xingxing Cheng; Zhenxing Wang (Adsorption Science & Technology)
Tetracycline (TC) is a commonly used antibiotic and enters the soil environment continuously. As humic acid (HA) is one of the most important components in soils, it is necessary to investigate the adsorption behavior of TC by HA under different conditions. In this paper, the factor of “aging” was considered. The methodology of coating CaCO3 precipitation on the surface of HA was adopted to simulate the aging process. The adsorption kinetics and isotherm demonstrated that the uptake of TC over HA was quicker with more amount than aged HA, meaning that aging affected the mass transfer of TC from the bulk solution to the outer surface of HA as well as from HA outer surface to its interior pores. To explain the effect of aging, BET was utilized to characterize the morphology of HA and aged HA. It was found that aging resulted in a decrease in specific surface area and pore size. XPS, FTIR, and 2D-COS revealed how aging influenced the chemical composition of HA. Five kinds of functional groups carried by HA contributed to the adsorption of TC, in which the binding affinity towards TC followed the order of −COO>N−H>−C−C>C−O>O−H. These results indicated that -COO was the most sensitive adsorption site. Compared to HA, the content of -COO for aged HA decreased obviously. In summary, aging affected the morphology and chemical position of HA and consequently lead to the change in adsorption kinetics and isotherm of TC.